Sistem Informasi Penilaian Akhir Mahasiswa Berbasis Web - Jemmy Edwin B (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2010)
Final assessment is one of the obligations of a lecturer and the right of a student in a lecture. Systems that are still often used today is the manual counting system and the use of paper as a medium to student publications. The manual system has the risk of delay when the lecturer must teach many courses with many students. Based on this fact, they invented a Final Assessment of Student Information System Web-based. This system can automate the final assessment. Gains derived from this system are, in addition to the automatic final assessment, students can learn the value of the college, faculty objectivity more guaranteed, and the use of paper can be minimized.